The Roles of the Branch Advisory Council on Students’ Interest in Scouting and Entrepreneurship - Hapsari, Maulani Mega; Martono, Trisno; Wardani, Dewi Kusuma; Noviani, Leny; Aedi, Nur (Journal of Ecohumanism, 2024)
Scouting, a globally recognized movement, has long been praised for fostering altruistic behavior among young people while instilling values such as leadership, collaboration, and community service. However, the influence of the Branch Advisory Council (Mabiran) on scouting, particularly regarding student interests and perceived entrepreneurial spirit, remains relatively unknown. This study aims to examine the relationship between Mabiran’s role, students’ participation in scouting activities, and their inclination toward entrepreneurship. Using a survey-based approach, the study seeks to explore essential components of Mabiran’s functions and their impact on student engagement in scouting activities and perceived entrepreneurial tendencies. Survey findings indicate that while Mabiran commonly provides guidance and support for scouting education, it lacks in establishing cooperation with the business and industry sectors. Despite this, students’ passion for scouting seems to be positively influenced by Mabiran’s involvement. To maximize its potential, Mabiran should adopt a more proactive approach to collaborating with business sectors, thereby enhancing opportunities for students’ entrepreneurial development.